An Error Analysis of Inflectional Affixes in Writing Analytical Exposition Text on Students at SMAN 3 Medan - Dewinarto Nainggolan; Rina Octavia Simarmata; Fenty Debora Napitupulu (PT. Pusmedia Group Indonesia, 2025)
This research is motivated by the finding that students of SMA Negeri 3 Medan often make mistakes in using inflectional affixes when writing, especially in the placement of affixes that can affect the quality of writing and message delivery. This research aims to analyze the misuse of inflexional affixes in analytical exposition texts written by SMA N 3 Medan students. Qualitative descriptive method is used to identify the types of errors and determine the dominant types of errors. The subjects of this study were 25 students of grade XI of SMA Negeri 3 Medan, but only 9 students' written works were analyzed as samples to obtain data on inflectional affixes errors. Data were obtained through the analysis of students' analytical exposition texts, with the results showing that the dominant error occurred in the addition category at 72%, followed by misformation at 20%, omission at 8%, and misordering at 10%. The most frequent errors were found in the use of morphemes such as -s, -es, -ly, and -ed that did not fit the rules. The findings show that students' lack of understanding of the function of inflectional affixes affects the quality of their writing, especially in delivering messages effectively. This research provides practical implications for teachers to improve teaching related to inflectional affixes and for students to better understand the importance of correct affix usage in writing texts. In addition, the results of this study can be a reference for other researchers who are interested in analyzing language errors, especially related to inflectional affixes, to support the development of more effective English learning methods in the future.